EFFECT OF COMPENSATION, LEADERSHIP, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT RONGOH ABADI - Jennifer Christian; Elsa Cendana; Khomeiny Yunior (Jurnal Mantik, 2022)
The purpose of the study was to examine and analyze the effect of Compensation, Leadership, and Work Discipline on Employee Performance at PT Rongoh Abadi. The decline in the performance of PT Rongoh Abadi's employees is caused by unsatisfactory compensation, ineffective leadership and low employee discipline. The population is 138 employees of PT Rongoh and the number of samples is 103 employees of PT Rongoh. The sampling technique used is simple random sampling. The data analysis technique in this study uses multiple linear regression analysis. Partial test results obtained tcount > ttable or 3.765 > 1.984 and significant obtained 0.000 <0.05, meaning that compensation has a positive and significant effect on employee performance at PT Rongoh Abadi. Partial test results obtained tcount > ttable or 2,533 > 1,984 and significant obtained 0,013 < 0,05, meaning leadership has a positive and significant effect on employee performance at PT Rongoh Abadi. Partial test results obtained tcount > ttable or 4.029 > 1.984 and significant obtained 0.000 <0.05, meaning that work discipline has a positive and significant effect on employee performance at PT Rongoh Abadi. The test results simultaneously obtained the calculated F value (22.672) > F table (2.70) and a significance probability of 0.000 <0.05, meaning that compensation, leadership, and work discipline have a positive and significant effect on employee performance at PT Rongoh Abadi. Employee performance that can be explained by variations in compensation variables.